GRIN lens implantation strategies for in vivo calcium imaging using miniature microscopy - Pingping Zhao; Daniel Aharoni; Peyman Golshani (PLoS ONE, 2025)
Miniature microscopy (Miniscope) has become one of the most popular and valuable neuroscience tools in the last decade. Miniscope in vivo calcium imaging during freely moving behavior has led to a number of transformative discoveries about neural coding across a large range of behaviors. The UCLA Miniscope Project is an open-source miniaturized microscopy platform that has greatly benefited the neuroscience community and led to the release of a number of different miniaturized microscopes with extended capabilities. While researchers can record from essentially any brain region through a cranial window or a gradient index of refraction (GRIN) lens, there is still a need for comprehensive protocols which describe detailed surgical procedures for successful miniaturized microscopy applications across different brain regions. Here, we provide step-by-step surgical procedures for implantation of GRIN lenses to record from a number of different brain regions including subregions in the medial prefrontal cortex (PrL, IL, DP), subregions in the hippocampus (dCA1, CA2 and vCA1), and the ventral striatum (nucleus accumbens, NAc). Moreover, we also provide surgical methods of new multi-brain regions imaging techniques developed by our group to record bilateral medial prefrontal cortex (mPFCs) or simultaneously record mPFC and NAc. Taken together, this protocol details easy and reproducible techniques for GRIN lens implantation and miniaturized microscopy in multiple structures.